2017
DOI: 10.1161/jaha.116.004897
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effects of Centrally Administered Angiotensin II are Enhanced in a Mouse Model of Alzheimer Disease Independently of Blood Pressure

Abstract: BackgroundThe significance of brain angiotensin II in Alzheimer disease (AD) is unclear.Methods and ResultsTo examine the role of brain angiotensin II in AD, intracerebroventricular angiotensin II infusion was performed on 5XFAD mice, a mouse model of AD, and wild‐type mice, and the detrimental effects of brain angiotensin II was compared between the 2 strains of mice. Intracerebroventricular angiotensin II infusion significantly impaired cognitive function in 5XFAD mice but not in wild‐type mice. This vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 51 publications
5
32
0
1
Order By: Relevance
“…AngII infusion impaired both Wt-AngII and Tg-AngII rats in the MWM adaptation of a delayed match-sample test, a spatial task that tests working memory and behavioral flexibility, consistent with the clinical studies on the cognitive effects of hypertension (Raz et al, 2003;Vicario et al, 2005;Li et al, 2016). Previous studies have found histological and cognitive effects of AngII infusion or AngII blockade to be independent of blood pressure, which has been attributed to the central effects of AngII (Tedesco et al, 2002;Iadecola and Gorelick, 2004;Takeda et al, 2009;Capone et al, 2011;Hajjar et al, 2012;Takane et al, 2017), though these studies did not explicitly assess for white matter changes. It remains a possibility that high blood pressure alone, independently of AII, induces astrocytosis in the WM.…”
Section: Discussionsupporting
confidence: 83%
“…AngII infusion impaired both Wt-AngII and Tg-AngII rats in the MWM adaptation of a delayed match-sample test, a spatial task that tests working memory and behavioral flexibility, consistent with the clinical studies on the cognitive effects of hypertension (Raz et al, 2003;Vicario et al, 2005;Li et al, 2016). Previous studies have found histological and cognitive effects of AngII infusion or AngII blockade to be independent of blood pressure, which has been attributed to the central effects of AngII (Tedesco et al, 2002;Iadecola and Gorelick, 2004;Takeda et al, 2009;Capone et al, 2011;Hajjar et al, 2012;Takane et al, 2017), though these studies did not explicitly assess for white matter changes. It remains a possibility that high blood pressure alone, independently of AII, induces astrocytosis in the WM.…”
Section: Discussionsupporting
confidence: 83%
“…ANG II signaling through AT 1 R promotes neuroinflammation in a mouse model of Alzheimer's disease termed 5X familial AD (5XFAD). ICV infusion of ANG II impaired cognitive function in 5XFAD mice, which was associated with hippocampal inflammation, oxidative stress, and increased amyloid-␤ deposition (1029). Telmisartan prevents neuroinflammation by suppression of lipopolysaccharideinduced NO production from inducible NO synthase, and TNF-␣ and IL-1␤ secretion by BV2 microglia.…”
Section: Ang II Signaling In Cognitive Dysfunction Dementia and mentioning
confidence: 94%
“…Studies performed in vitro have shown that Ang-II reduces BBB permeability and promotes tight junction expression in developing BBB endothelial cell monolayers (Wosik et al, 2007), but increases permeability when added to already established monolayers (Fleegal-DeMotta, Doghu, & Banks, 2009). BBB-disruptive effects of Ang-II were also found in vivo, though in the context of injury, disease (Takane et al, 2017), or pre-induced hypertension. In these models, Ang-II was introduced either directly into the CNS via infusion (Li et al, 2016) or indirectly via BBB disruption (Biancardi, Son, Ahmadi, Filosa, & Stern, 2014)that permitted entry of Ang-II (alongside other blood-borne factors) from circulation.…”
Section: Do Astrocyte-secreted Factors Maintain the Blood-brain Barrier?mentioning
confidence: 96%